Специфіка пенсійного забезпечення окремих категорій громадян в Україні - Олеарчик, Софія Володимирівна; Olearchyk, Sofiia Volodymyrivna (Національний університет "Львівська політехніка", 2024)
Пенсійне забезпечення окремих категорій громадян в Україні є важливим аспектом соціальної політики держави, що потребує особливої уваги та вдосконалення, особливо в контексті військових дій та економічних викликів. Існуюча система пенсійного забезпечення характеризується нерівномірністю та недостатньою узгодженістю підходів до різних категорій громадян, зокрема військовослужбовців, державних службовців, науковців та інших професійних груп, що створює соціальну напругу та потребує системного реформування (Михайлова, 2023). Актуальність дослідження обумовлена також імплементацією міжнародних стандартів у національне законодавство України та необхідністю гармонізації вітчизняної системи пенсійного забезпечення з європейськими нормами в рамках євроінтеграційних процесів. Особливого значення набуває забезпечення соціальної справедливості та фінансової стійкості пенсійної системи з урахуванням специфічних потреб окремих категорій громадян, що вимагає комплексного наукового аналізу та розробки ефективних механізмів реалізації (Ткаченко & Петренко, 2024). Об'єкт дослідження:є система пенсійного забезпечення в Україні на сучасному етапі. Предмет дослідження: особливості пенсійного забезпечення людей похилого віку в Україні. Мета бакалаврської кваліфікаційної роботи: дослідити на теоретичному та емпіричному рівнях особливості пенсійного забезпечення осіб похилого віку в Україні. Гіпотеза дослідження. Система пенсійного забезпечення окремих категорій громадян в Україні потребує вдосконалення через наявні правові колізії та економічні обмеження, які призводять до соціальної несправедливості та фінансової нестабільності пенсійного фонду. Результати дослідження: Дослідження розкриває теоретико-правові аспекти пенсійного забезпечення окремих категорій громадян в Україні, виявляючи суттєві недоліки в чинній системі та визначаючи механізми призначення й виплати пенсій особам пенсійного віку. Аналіз ефективності діяльності Пенсійного фонду України за 2021-2025 роки демонструє значні фінансові та демографічні проблеми, пов'язані з недостатньою збалансованістю пенсійної системи, що підтверджує необхідність її подальшого реформування шляхом розвитку накопичувального рівня, удосконалення солідарної системи та підвищення фінансової стійкості Пенсійного фонду для забезпечення гідного рівня життя пенсіонерів.

Pension provision for certain categories of citizens in Ukraine is an important aspect of the state's social policy, which requires special attention and improvement, especially in the context of military operations and economic challenges. The existing pension provision system is characterized by unevenness and insufficient coordination of approaches to different categories of citizens, in particular military personnel, civil servants, scientists and other professional groups, which creates social tension and requires systemic reform (Mykhaylova, 2023). The relevance of the study is also due to the implementation of international standards in the national legislation of Ukraine and the need to harmonize the domestic pension provision system with European standards within the framework of European integration processes. Of particular importance is ensuring social justice and financial sustainability of the pension system, taking into account the specific needs of individual categories of citizens, which requires a comprehensive scientific analysis and development of effective implementation mechanisms (Tkachenko & Petrenko, 2024). Object of research: the pension system in Ukraine at the present stage. Subject of research: features of pension provision for the elderly in Ukraine. The purpose of the bachelor's qualification work: to investigate at the theoretical and empirical levels the features of pension provision for the elderly in Ukraine. Research hypothesis. The pension system for individual categories of citizens in Ukraine needs improvement due to existing legal conflicts and economic restrictions that lead to social injustice and financial instability of the pension fund. Research results: The study reveals the theoretical and legal aspects of pension provision for individual categories of citizens in Ukraine, identifying significant shortcomings in the current system and determining the mechanisms for assigning and paying pensions to persons of retirement age. The analysis of the effectiveness of the Pension Fund of Ukraine for 2021-2025 demonstrates significant financial and demographic problems associated with the insufficient balance of the pension system, which confirms the need for its further reform by developing the accumulative level, improving the solidarity system and increasing the financial stability of the Pension Fund to ensure a decent standard of living for pensioners.
Specifics of pension provision for certain categories of citizens in Ukraine
Keywords: 6.232.00.00; Пенсійне забезпечення; окремі категорії громадян; пенсійна система; пільги; пенсійний вік; доходи; бюджет; Пенсійний фонд України; Pension provision; certain categories of citizens; pension system; benefits; retirement age; income; budget; Pension Fund of Ukraine. List of sources used Mykhaylova; I. Yu. (2023). Modern problems of pension provision for certain categories of citizens in Ukraine. Law of Ukraine; 4(2); 78-95. URL: https://univer.km.ua/profile/mykhaylova-iryna-yuriyivna Tkachenko; O. V.; & Petrenko; S. M. (2024). European standards of pension provision and their implementation in the legislation of Ukraine. Law and Society; 1; 112-126. URL:https://ipacs.knu.ua/pages/osn/2/news/2184/files/f1befd39-12f8-4f1f-b0bc-15192dd1d260.pdf Shevchenko; N. P. (2022). Reforming the pension provision of certain categories of citizens: problems and prospects. Scientific Bulletin of Uzhgorod National University. Series: Law; 73; 201-208. URL https://elar.navs.edu.ua/server/api/core/bitstreams/768170a4-9532-46b3-9128-e99b3ae7ff64/content